(3EfHGg GdQhGI Ydi CfHGA GdfMGIs - (3Ydj Hf jhSa Hf EHQGgje GdTjHGfj GdbaWj, CHh GdMSf, LeGd GdOjf,J (B646 (3g` s
(3ChdgG (B:s
(3GdaVd Hf GdMHGH CHh NdjaI GdLei cGf CMO GUMGH GdMOjK hGSY GdQhGjI s
(3BNQgG (B:s
(3hcGf efUakG hdg gfGc TgQI XGgQI hJfGaS Cgd GdBOH ai JMUjd eUfaGJg hjJRGMehf Ydi GOQGc ahGjOg Je GdcJGH s
(3fSNI KGfjI eUhQI Yf fSNI WhHbHh SQGi (B2858s
(3HGdBSJGfIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B33 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B263s
Keywords: (3GdJGQjNs